PENGARUH ANOMALI KARAKTERISTIKA HUJAN TERHADAP EROSI LAHAN (Studi Kasus DAS Merawu, Jawa Tengah) - Marhendi, Teguh (UMP, 2011)
Global climate change is an important issue that is still a lot of attention in the last decade. Indonesia can not be separated from the problem of global climate change. Climate change has caused some irregularities, such as increased air temperature, evaporation and rainfall. One of the impacts of global climate change is the emergence of anomalies characteristics rain, including the Merawu Watershed which is one Mrica Reservoir catchment area is eroding the land is quite high and changeable. Changes in erosion is influenced by many factors such as increasing factors of land use, land as well as factors characteristics rain. Global climate change which affects the onset of the rainy characteristics anomaly, believed to give effect to changes in the rate of erosion in the Merawu watershed. Throughout 1989 to 2009 the highest annual rates of erosion occurred in 2001 amounting to 16.41 mm / year and the lowest occurred in 1996 amounting to 5.00 mm / year.This paper is intended to assess the influence of rain characteristicsÂ anomaly, namely the intensity and duration of rainfall, as well as its influence on soil erosion occurring in the Merawu Watershed. The review begins with the preparation of anomalous nature of abnormality criteria daily or monthly rainfall. The next study is related to patterns of erosion associated with the phenomenon of rain, followed by the rate of erosion predictions with respect to the existence of the rainfall anomalies. Analyses were performed on the anomalous nature of characteristics rain using 2002 data, considering 2002 was a year of El Nino with the criteria being, with comparative data in 1992, 1996, 1998 and 2005.The results of the analysis for 2002 data, overall rainfall anomaly characteristics show negative anomalies except in March, April, September, November and December. In January, February, May, July, August and October have characteristics rainfall anomalies are very dry until it reaches -320 mm /month. In this condition has decreased soil erosion. Positive rainfall anomalies characteristics occurred in March, April, September, October and November with the highest anomalies of 216 mm/ month. This condition causes the erosion of the month have increased. Keyword: Merawu watershed, Anomaly characteristics rain, soil erosion